121k views
5 votes
Express f(x) in the form f(x) = (x - k)q(x) +r for the given value of k.

f(x) = 4x^3+ x² + x-8, k= -1

1 Answer

0 votes

Answer:

f(x) = (x + 1)*(4*x² - 3*x + 4) - 12

Explanation:

We have:

f(x) = 4*x³ + x² + x - 8

We want to write this in:

f(x) = (x - k)*q(x) + r.

with k = -1

Then we want to write:

4*x³ + x² + x - 8 = (x - (-1))*q(x) + r

4*x³ + x² + x - 8 = (x + 1)*q(x) + r

Because f(x) is polynomial of degree 3, we know that q(x) must be a polynomial of degree 2.

then:

q(x) = a*x² + b*x + c

Then:

4*x³ + x² + x - 8 = (x + 1)*(a*x² + b*x + c) + r

4*x³ + x² + x - 8 = a*x³ + b*x² + c*x + a*x² + b*x + c + r

if we take common factors in the right side we get:

4*x³ + x² + x - 8 = a*x³ + (b + a)*x² + (c + b)*x + (c + r)

Now, we must have:

4*x³ = a*x³

then:

4 = a

We also must have:

x² = (b + a)*x²

1 = (b + 4)

1 - 4 = b

-3 = b

We also must have:

x = (c + b)*x

1 = (c + (-3))

1 + 3 = c

4 = c

And finally:

- 8 = (c + r)

-8 = 4 + r

-8 - 4 = r

-12 = r

Then:

f(x) = (x + 1)*(4*x² - 3*x + 4) - 12

User K P
by
4.6k points